Benchmarking Psychosocial Skills Important for Talent Development. Issue 168 (29th October 2019) - Olszewski‐Kubilius, Paula; Subotnik, Rena F.; Davis, Lauren Cassani; Worrell, Frank C.
Abstract: How can high potential in childhood be transformed into outstanding adult accomplishment? Research indicates that individuals who become outstanding performers and producers have more than just raw talent in the domain or opportunities to develop their talent—they have the will, drive, and focus to take advantage of the opportunities with which they are presented, and the capacity to persist through failures even as the bar for success gets higher. Despite the importance of these psychosocial facilitators, they are among the least well understood in the field of gifted and talented research. In this study, we reviewed existing literature in order to build comprehensive list of the psychosocial variables associated with talent development across domains (visual art, dance, sports, academics, music, acting, medicine, and software engineering). With the help of psychologists with expertise in these domains, we completed an initial categorization of these skills and asked the experts to indicate at which of the three stages in talent development—the transition of abilities into competencies, competencies into expertise, and expertise to creative productivity or eminence—each psychosocial skill was important. We found promising general patterns of commonality as well as variation by domain and stage of talent development, and discuss the implications of this study on future research into psychosocial skill development.